Conformational flexibility of RNA polymerase III during transcriptional elongation - Fernández‐Tornero, Carlos; Devos, Damien (The EMBO journal, 2010)
RNA polymerase (Pol) III is responsible for the transcription of genes encoding small RNAs, including tRNA, 5S rRNA and U6 RNA. Here, we report the electron cryomicroscopy structures of yeast Pol III at 9.9 Å resolution and its elongation complex at 16.5 Å resolution. Particle sub‐classification reveals prominent EM densities for the two Pol III‐specific subcomplexes, C31/C82/C34 and C37/C53, that can be interpreted using homology models. While the winged‐helix‐containing C31/C82/C34 subcomplex initiates transcription from one side of the DNA‐binding cleft, the C37/C53 subcomplex accesses the transcription bubble from the opposite side of this cleft. The transcribing Pol III enzyme structure not only shows the complete incoming DNA duplex, but also reveals the exit path of newly synthesized RNA. During transcriptional elongation, the Pol III‐specific subcomplexes tightly enclose the incoming DNA duplex, which likely increases processivity and provides structural insights into the conformational switch between Pol III‐mediated initiation and elongation.